Association between changes in walking time and all-cause mortality among survivors of the Great East Japan Earthquake: the Research Project for Prospective Investigation of Health Problems Among Survivors of the Great East Japan Earthquake and Tsunami Disaster (RIAS) study - Kiyomi Sakata; Kozo Tanno; Junji Kuno; Megumi Tsubota-Utsugi; Haruki Shimoda; Eri Takusari; Nobuyuki Takanashi; Toshiyuki Onoda (BMJ Public Health)
Introduction Several studies have investigated the association between physical activity (PA) and all-cause mortality. However, no study has systematically examined the association between PA changes and all-cause mortality among residents of disaster-stricken areas. This study aimed to clarify the association between PA changes and the risk of all-cause mortality among survivors of the Great East Japan Earthquake.Methods At two time points from 2011 to 2012, 2138 men and 3683 women responded to a question about walking time. The cut-off value was set at 30 min, and PA changes were evaluated using responses regarding walking time over 2 years. Participants were classified into four groups according to PA changes: high stable, increasing, decreasing and low stable. Using a Cox regression model, multivariate-adjusted HRs and 95% CIs for all-cause mortality, according to PA changes, were calculated after adjusting for age, area, smoking status, drinking status, grip strength, psychological distress, obesity, hypertension, diabetes, dyslipidaemia, residential status and current job status.Results During the 5-year follow-up, 241 deaths occurred. Compared with that of the high stable group, the decreasing group had a higher risk of all-cause mortality; multivariate-adjusted HRs were 2.40 and 2.43 for men and women, respectively. Among women, the low stable group also had a higher risk of all-cause mortality compared with that of the high stable group.Conclusion Our findings indicate the importance of assessing PA and creating an environment to allow its maintenance as early as possible after large-scale natural disasters.